Diffusion Weighted MRI by Spatiotemporal Encoding: Analytical Description and In Vivo Validations - Solomon, Eddy (J Magn Reson, 2013)
Diffusion-Weighted (DW) MRI is a powerful modality for studying microstructure in normal and pathological tissues. DW MRI, however, is of limited use in regions suffering from large magnetic field or chemical shift heterogeneities. Spatio-temporal encoding (SPEN) is a single-scan imaging technique that can deliver its information with a remarkable insensitivity to field inhomogeneities; this study explores the use of diffusion-weighted SPEN (dSPEN) MRI as an alternative for acquiring this kind of information. Owing to SPEN’s combined use of gradients and radiofrequency-swept pulses, spatially-dependent diffusion weightings arise in these sequences that are not present in conventional k-space DW MRI. In order to account for these phenomena an analytical formalism is presented that extends Stejskal & Tanner’s and Karlicek & Lowe’s work, to derive the b-values arising upon taking into account the effects of adiabatic pulses, of imaging as well as diffusion gradients, and of cross-terms between them. Excellent agreement is found between the new features predicted by these analytical and numerical derivations, and SPEN diffusion experiments in phantoms and in anisotropic ex vivo systems. Examinations of apparent diffusion coefficients in human breast volunteers also verify the advantages of the new methods in vivo, which exhibit substantial robustness vis-à-vis comparable DW echo planar imaging.